The plundered planet how to reconcile nature with prosperity - Collier, Paul. (Oxford Oxford University Press, 2010)
How can we help poorer countries become richer without harming the planet? Is there a way of reconciling prosperity with nature? World-renowned economist Paul Collier offers smart, surprising and above all realistic answers to this dilemma. Steering a path between the desires of unchecked profiteering and the romantic views of environmentalists, he explores creative ways to deal with poverty, overpopulation and climate change -showing that the solutions needn't cost the earth. The book proposes a radical rethinking of international policies and uniquely, offers real solutions backed up by real data from research Collier has spearheaded
Includes bibliographical references (p. [245]-247)
Keywords: Natural resources-Management.